Understanding and Ability to Apply Occupational Safety and Health Principles at Construction Workshops in Tabanan - Diah Gayatri Sudibya; I Gusti Ketut Sri Astiti; Kade Richa Mulyawati (Fakultas Hukum, Universitas Warmadewa, 2022)
In general, this program is designed by Warmadewa University to make a real contribution to the nation by carrying out various forms of activities that can be carried out in groups or individually. In terms of community service activities, there is a sense of caring from campus elements who know directly to the community. One of the things that caught our attention from the campus element in the field of Law, was to provide socialization and Legal Counseling on Occupational Safety and Health or known as K3. Where in the Manpower Act, the Preamble considers the letters c and d of Law No. 13 of 2003, it is stated that, in the implementation of National Development, the workforce has a very important role and position as actors and development goals. For this reason, labor protection is intended to guarantee the basic rights of workers/laborers and ensure equality, opportunity and treatment without discrimination on any basis to realize the welfare of workers, in this case occupational safety and health, to realize the welfare of workers/laborers and their families with due regard to development of the business world. The formulation of the problems that arise: 1) There is no in-depth understanding of occupational safety and health regulations which are the operational standards of work implementation for workers. 2) Workers feel uncomfortable using personal protective equipment for occupational safety and health. In the end, this program can provide the basis for changes in the implementation of the laws that apply to the Assoka Wijaya workshop company located in Tabanan district so that the safety and health of workers can be guaranteed.